DIVERSITY OF DRAGONFLY AROUND THE AYUNG RIVER - Trisna, Ayu Wulan; Watiniasih, Ni Luh; Ginantra, I Ketut (SIMBIOSIS; Vol 10 No 1 (2022)DO - 10.24843/JSIMBIOSIS.2022.v10.i01.p06, 2022)
This research was conducted from february to April 2020 in three different areas, including in Petang in Penikit Village, Sayan Village, Ubud, and in Padang Galak Village, Sanur using sweeping techniques. This study aims to determine the diversity of dragonflies along the Ayung river. The analyzes carried out include analyzing the Shannon-Wiener diversity index (H'), evenness index (E), dominance index (D) sympons, frequency of presence and water quality of the Ayung River. The results showed as many as 11 species of dragonflies. The most common individuals found were Orthetrum Sabina (23 individuals), while the lowest individuals were from the Libellulidae family as many as 5 individuals. Most species and individuals were found at the Sayan location with 11 species with a total of 124 individuals (H'=2.24, E=0.93, D=0.19), followed by 6 species in the Petang location with a total of 27 individuals (H' =1.60, E=0.89, D=0.30), while the lowest was the Sanur location with 4 species with a total of 15 individuals (H'=0.94, E=0.69, D=0.67 ). Diversity of dragonflies in the Ayung River is classified as moderate (H'=2.36), the evenness index of species at the Petang and Sayan locations is in the almost evenly distributed category. Petang (0.89) and Sayan (0.93), while the Sanur location was in the fairly even category (0.69). The highest frequency of presence in Orthetrum sabina species was 89% with frequent or absolute presence categories. The BOD and DO values ??in the Ayung River do not meet the requirements of water quality standards, while COD meets the requirements based on PP No. 82 of 2001. Keywords: Diversity, dragonflies, Ayung River.